The Effects of Online Physical Activity During Covid-19 Pandemic among Undergraduate Students in Thailand - Hemarachatanon, Poramet; Nuttouch, Wattana; Weerawong, Neeranoot; Huntula, Soontaraporn (Physical Education Theory and Methodology, 2023)
Study purpose. The purpose of this study was to develop a physical activity program by using resistance band for students to improve physical activity and monitor improvements in physical performance. The university students’physical activity, which was still low before the pandemic, may be impacted by these. As a result, we want to incorporate physical activity into our course and assess the differences in physical performance before and after taking the course. Materials and methods. 95 undergraduate college students signed up to take the course. The online course, which included resistance band training for a total of 12 weeks, addressed the principles of resistance band training/exercise. The physical performance of the participants was assessed both before and after training. Results. According to our study findings, university students at Walailak University can increase their physical performance by using an online resistance band training. The physical fitness statistics for the wall sit test, sit up test, sit and reach test, and shuttle run test were significantly different before and after the online elastic band intervention (p=0.0463, p=0.0050, and p=0.0430, respectively), but not for the shuttle run or YMCA 3-minute step test. Conclusions. The results of this study provide proof that resistance band training improves strength and encourages physical activity. In order to reduce anxiety and depression, which the COVID-19 has severely touched, as well as to increase the population’s level of physical activity or exercise, we must continually promote physical activity or exercise at home.